Case report: Primary cytomegalovirus infection in a patient with late onset multiple sclerosis treated with dimethyl fumarate - Muñoz, Julia Sabin; Santiago, Alberto Díaz-De; Escudero, José Cebrián; Merino, J. A. García (Frontiers in Neurology, 2024)
Background Treatment of multiple sclerosis (MS) with delayed-release dimethyl fumarate (DMF) has shown efficacy and safety in clinical trials. However, the occurrence of infectious complications, particularly in elderly patients, remains a concern. Methods We present the case of a 63-year-old woman with late-onset MS treated with DMF, who developed a severe primary cytomegalovirus (CMV) infection. DMF was discontinued, and antiviral treatment was initiated, resulting in complete resolution of symptoms. Results While DMF is generally considered safe in terms of opportunistic infections, this case highlights the possibility of serious infectious complications in eldery DMF-treated patients, even without documented lymphopenia. Conclusion Advanced age and the associated immunological changes may contribute to an inadequate immune response to MS treatments, highlighting the importance of a careful treatment choice in elderly patients with MS. Further research and specific data on the safety and efficacy of DMF in this population are required to guide clinical decision-making.